2012
DOI: 10.1371/journal.pone.0032684
|View full text |Cite
|
Sign up to set email alerts
|

Pentachlorophenol Induction of the Pseudomonas aeruginosa mexAB-oprM Efflux Operon: Involvement of Repressors NalC and MexR and the Antirepressor ArmR

Abstract: Pentachlorophenol (PCP) induced expression of the NalC repressor-regulated PA3720- armR operon and the MexR repressor-controlled mexAB-oprM multidrug efflux operon of Pseudomonas aeruginosa . PCP's induction of PA3720- armR resulted from its direct modulation of NalC, the repressor's binding to PA3720- armR promoter-containing DNA as seen in electromobility shift assays (EMSAs) being obviated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…MarR homologues control pathways that are critical to bacterial physiology such as stress responses (41,42), virulence (43), metabolism (10), and multiple-drug resistance (23,44,45). The activity of a subset of these proteins can be modified through the formation of a disulfide bond (19,41,46).…”
Section: Discussionmentioning
confidence: 99%
“…MarR homologues control pathways that are critical to bacterial physiology such as stress responses (41,42), virulence (43), metabolism (10), and multiple-drug resistance (23,44,45). The activity of a subset of these proteins can be modified through the formation of a disulfide bond (19,41,46).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data, however, showed that pentachlorophenol stimulates MexABOprM production, surprisingly, in an ArmR-independent (although MexR-dependent) manner (809). Possibly, the regulatory pathway here involves in vivo-generated catabolite effectors mimicking more specific antimicrobial phenolic compounds than pentachlorophenol that P. aeruginosa may encounter in its natural environment (809). The physiological conditions under which ArmR ultimately activates mexAB-oprM thus remain unclear and require further studies.…”
Section: P Aeruginosa Efflux Pumpsmentioning
confidence: 99%
“…However, chemostat experiments with strain PAO1 showed that various chlorinated phenols, including the environmental contaminant pentachlorophenol, can induce the expression of the PA3720-PA3719 and mexAB-oprM operons through reversible, noncovalent binding to the NalC protein (807,808). Recent data, however, showed that pentachlorophenol stimulates MexABOprM production, surprisingly, in an ArmR-independent (although MexR-dependent) manner (809). Possibly, the regulatory pathway here involves in vivo-generated catabolite effectors mimicking more specific antimicrobial phenolic compounds than pentachlorophenol that P. aeruginosa may encounter in its natural environment (809).…”
Section: P Aeruginosa Efflux Pumpsmentioning
confidence: 99%
“…Expression of mexAB-oprM is also induced by chlorinated phenols like pentachlorophenol (Ghosh et al 2011;Muller et al 2007;Starr et al 2012), an uncoupler of oxidative phosphorylation that may also promote oxidative stress that impacts the redox-sensitive MexR repressor. Pentachlorophenol has, for example, been shown to dramatically increase O 2 flux in P. aeruginosa, generating an oxidative stress that could impact MexR activity (McLamore et al 2010).…”
Section: Effluxmentioning
confidence: 99%